(untitled) (Training and Practice : Journal of Educational Sciences, 2013)
Our students and young people in general use a lot of expressions that prove to be new for older generations. The paper gives an analysis of relatively new Hungarian verbal coinages with the prefix be. The study of example sentences shows that the meaning of the prefix be in newly coined verbal expressions cannot be explained by the principle of compositionality bcause the sum of the meanings of the elements of a phrase (prefix and verb) does not equal the meaning of the whole unit (phrase). However, if we think of such phrases not as linguistic units but as units of thought and use the principle of motivation, the meaning of new coinages can be revealed. The present study attempts to do so in a cognitive semantic framework.